Analysis of factors that could affect symptomatic outcome in patients having laparoscopic excision of deep rectovaginal endometriosis in BSGE endometriosis centres. (June 2021) - Byrne, D.L.; Curnow, T.L.; Vashisht, A.; Clark, T.J.; ,
Abstract: Objective: Investigate factors that influence quality of life after laparoscopic excision of deep rectovaginal endometriosis. Study design: A multicentre prospective cohort study involving 63 hospitals accredited as British Society for Gynaecological Endoscopy specialist endometriosis centres was conducted. The study population comprised of 8368 women who had undergone laparoscopic surgical excision of deep rectovaginal endometriosis requiring dissection of the pararectal space. The main outcome assessed was mean quality of life measured using the EuroQol 100 mm visual analogue score at 6 and 24 months after surgery according to potential prognostic factors. These factors included patient characteristics (age, smoking status, BMI), previous treatments for endometriosis, concomitant bowel surgery and surgical complications. Results: Quality of life improved from a mean pre-operative score of 55/100 to 72/100 (p < 0.01), at 6 months following surgery and this elevated score was sustained at 24 months (mean VAS = 71/100; p < 0.01). Smoking and previous surgery for endometriosis were associated with significantly reduced quality of life at both 6 months (mean difference −7.7 (standard error (SE) 1.0); P < 0.01 and -2.8 (SE 0.7); P < 0.01 respectively) and 24 months after surgery (mean difference −6.8 (SE 1.8); P < 0.01 and −4.5 (SE 1.2); P < 0.01 respectively). Age over 45 years was predictive of greater clinical improvement at 6 and 24 months (mean difference 5.5 (SE 1.2); P < 0.01 and 9.7 (SE 2.2); P < 0.01) as was the use of gonadotrophin analogues (GnRHa) (mean difference 7.6 (SE 1.2); P < 0.01 and 8.9 (SE 2.0); P < 0.01). Conclusion(s): Laparoscopic excision of deep endometriosis in specialist centres improves quality of life. Women should be advised to stop smoking and consider pre-operative ovarian suppression. Surgery should be avoided prior to referral to a specialist centre in women diagnosed with deep rectovaginal endometriosis to achieve a better quality of life outcome.